PEMBUATAN OLAHAN TEPUNG SINGKONG DI DESA TRI JAYA: PROCESSING CASSAVA FLOUR IN TRI JAYA VILLAGE - Mahasiswa KKN Universitas Lampung (FMIPA Unila, 2025)
Tri Jaya Village is a village located in Penawar Tama District, Tulang Bawang Regency. Tri Jaya Village consists of 4 RKs and the majority of residents grow cassava plants in their respective yards. The aim was to hold socialization on making cassava leaf flour which was then substituted for cassava leaf flour sponge cake so that PKK women could know the technique of making cassava leaf flour which could be used as a raw material for processed food products. This flour can enrich the nutrition of sponge cake with fiber, vitamins and minerals from cassava leaves. Using cassava leaf flour can also provide a unique aroma and taste to sponge cake, creating an interesting and healthier variation. The advantages of steamed cassava leaf flour cake are that it adds selling value to cassava leaves, utilizes cassava leaves which are only used for animal feed and increases the nutritional content of a processed product. The disadvantage of steamed cassava leaf flour cake is that many people don't like the taste of cassava leaves. Keywords: Lampung University KKN, Lunik, Cassava Leaf Bolu, Cassava Leaf Flour, Cassava Plants, Cassava, Tri Jaya Village